Routes and methods of neural stem cells injection in cerebral ischemia - Xing‐Yu Yang; Xiao Zhang; Jun‐Feng Cao; Mei Wu; Sheng‐Yan Chen; Li Chen (Ibrain, 2023)
Abstract Cerebral ischemia is a serious cerebrovascular disease with the characteristics of high morbidity, disability, and mortality. Currently, stem cell therapy has been extensively applied to a wide range of diseases, including neurological disorders, autoimmune deficits, and other diseases. Transplantation therapy with neural stem cells (NSCs) is a very promising treatment method, which not only has anti‐inflammatory, antiapoptotic, promoting angiogenesis, and neurogenesis effects, but also can improve some side effects related to thrombolytic therapy. NSCs treatment could exert protective effects in alleviating cerebral ischemia‐induced brain damage and neurological dysfunctions. However, the different injection routes and doses of NSCs determine diverse therapeutic efficacy. This review mainly summarizes the various injection methods and injection effects of NSCs in cerebral ischemia, as well as proposes the existing problems and prospects of NSCs transplantation.